Towards inclusive campus mobility: strategic challenges faced by students with disabilities at UiTM Seremban - Awalluddin, Muhammad Aiman; Mohd Arshad, Mohd Ramlan; Jefri, Jasmin Irdina; Radzuan, Zamimie Fatin Amiera (Universiti Teknologi MARA, Perlis, 2025)
This study explores the transportation barriers faced by university students with disabilities (PWDs) in Malaysian universities, particularly at Universiti Teknologi MARA Seremban, highlighting how these challenges impact their mobility and social inclusion. Despite policy efforts aimed at promoting inclusivity, lived realities reveal systemic infrastructural, attitudinal, and financial constraints that continue to marginalize PWD students. Utilizing a qualitative phenomenological approach, semistructured interviews were conducted with five students with diverse disabilities in UiTM, Seremban. Findings indicate three major themes: inadequate transport infrastructure (e.g., non-functional elevators, lack of universal design), negative societal perceptions (e.g., stigma, lack of staff training), and high transport costs especially for e-hailing services used as alternatives to inaccessible public transit. These barriers disrupt students’ independence, punctuality, and participation in academic and extracurricular activities. The study underscores that transportation access is not merely a logistical concern but a matter of social justice, closely linked to educational equity and national development goals under the MADANI framework. It calls for collaborative interventions between universities, transport authorities, and policymakers to implement universal design standards, conduct disability sensitivity training, and provide financial support for accessible mobility. The study offers empirical insights to inform inclusive campus planning and national transport policies that reflect the lived experiences of students with disabilities.